Ezra Pound’s The River Merchant’s Wife: Representations of a Decontextualized “Chineseness” - Tang, Jun (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2011)
This article provides a detailed comparison of various interpretations of The River Merchant’s Wife: A Letter presented by Western scholars and the widely-recognized interpretation in the field of classical Chinese studies concerning its Chinese source text Changgan Xing. Analyzing the discrepancies between the two texts from a cross-cultural perspective, this article argues that The River Merchant’s Wife has produced a decontextualized “Chineseness” by using Japanized romanizations, manipulating cultural details, and changing the original messages. Consequently, Ezra Pound’s rewriting and manipulation have induced misunderstandings regarding the Chinese source text and have reinforced stereotypical preconceptions of gender image and married life in ancient China.